Pengaruh penggunaan metode manual dan retort klin terhadap karakteristik kimia biochar limbah kelapa sawit - Ratnasari, Ika Fitriana Dyah; Devi, Devi; Ismoyojati, Roni; Febriansyah, Ilham (Universitas Musamus, Merauke, Papua, 2024)
Oil palm is one of the world's strategic plantation commodities. Palm oil production continues to increase, which has implications for the increase in the amount of palm oil waste produced. One of the efforts to realize a sustainable palm oil program is by properly managing palm oil waste. Processing palm oil waste such as fronds, replanting trunks, and empty palm oil bunches with the pyrolysis method is one of the environmentally friendly waste processing. The use of the right method on each palm oil waste biomass determines the quality of the biochar produced. This study uses frond waste, replanting trunks, and empty palm bunches as raw materials for making biochar using pyrolysis methods, namely the manual method and Klin Retort. This study aims to determine the appropriate pyrolysis method to use through observation of the chemical characteristics of palm oil waste biochar. The results showed that the best chemical characteristics of palm oil waste biochar were in the Retort Klin method with a pH value and percentage of ash content, N-total, P-total, K-total, C-organic respectively of 7, 96, 4.86%, 0.47%, 0.04%, 0.96%, 50.18 on frond biochar, 7.42, 3.97%, 7.42%, 0.17%, 0.04%, 0.7%, 49.52% on replanting trunk biochar, and 6.31, 7.18%, 0.91%, 0.03%, 0.67%, 58.04% on oil palm empty bunch biochar. Keywords: oil palm, waste, biochar, pyrolysis